2020
DOI: 10.1016/j.corsci.2020.108488
|View full text |Cite
|
Sign up to set email alerts
|

Degradation behavior of Ti-Nb alloys: Corrosion behavior through 21 days of immersion and tribocorrosion behavior against alumina

Abstract: Non-toxic and allergic free β-type Ti alloys are attractive metallic implant materials due to their lower Young's modulus and good biocompatibility, but the corrosion and tribocorrosion behavior are yet to be fully understood. In this study, corrosion behavior of Ti-15Nb and Ti-40Nb alloys was investigated and compared with the commercial Ti-6Al-4V alloy through an immersion period of 21 days. The tribocorrosion behavior was investigated under open-circuit potential by using a ball-on-plate tribometer. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 44 publications
(57 reference statements)
3
30
0
Order By: Relevance
“…Several studies showed that Ti-6Al-4 V presents better wear resistance than the α + β Ti-15Nb [15], near β Ti-13Nb-13Zr [16], β Ti-12Mo-6 Zr-2Fe [17], and β Ti-29Nb-13Ta-4.6 Zr [18] mainly due to its higher hardness resulting from its microstructure. Under OCP conditions, the Ti-6Al-4 V alloy presented lower wear volume loss that may be linked to its higher hardness values compared to the Ti-12Nb alloys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that Ti-6Al-4 V presents better wear resistance than the α + β Ti-15Nb [15], near β Ti-13Nb-13Zr [16], β Ti-12Mo-6 Zr-2Fe [17], and β Ti-29Nb-13Ta-4.6 Zr [18] mainly due to its higher hardness resulting from its microstructure. Under OCP conditions, the Ti-6Al-4 V alloy presented lower wear volume loss that may be linked to its higher hardness values compared to the Ti-12Nb alloys.…”
Section: Discussionmentioning
confidence: 99%
“…The ingots were re-melted several times then heat treated at 1000°C for 24 h in an ultra-vacuum furnace for homogenization. Afterwards, the ingot was submitted to a hot-rolling treatment carried out at 900°C and, finally, another heat treatment at 1000°C for 24 h in a vacuum to relieve the residual stress during the machining procedure (complete details of the processing are given elsewhere [15]). In the case of the alloy produced by P/M, TiH 2 and Nb powders were homogenized by mixing for 1 h in a Turbula® multidirectional mixer.…”
Section: Materials and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical circuit selected in this study is commonly used to designate the EIS parameters for Ti-based materials in physiological solutions. [27,70] For all of the fitting data, v 2 values were less than 0.05. Designated values of CPE parameter (Y p ) were in the range of 10 À5 X À1 cm À2 s n , which is a typical for passive layers formed on Ti and its alloys tested in the biomedical solutions.…”
Section: Corrosion Responsementioning
confidence: 93%
“…An alumina ball (Oakwase Ltd., UK) was chosen as an inert counterface. This tribosystem does not represent a specific implant application, but rather serves as a baseline system for a comparative assessment of the tribocorrosion properties of the four chosen titanium alloys and for further comparison with other previously published work [22][23][24]. The test were performed at 37 °C in a simulated joint fluid consisting of new-born calf serum with a protein concentration of 15.5 g/L (First Link (UK) Ltd.…”
Section: Tribocorrosion Proceduresmentioning
confidence: 99%